THE DEVELOPMENT OF BISTRUCTURNIY ANALYS - L. A. Lebedeva (Научный вестник МГТУ ГА, 2016)
This article speaks about development of bistructurniy analys, which lets manager find concrete reason for inward conflict of worker, discover constructive withdrawal from this situation in behalf of organization, design for own interests of worker and draw a conclusions, which must be conducive to effective being at the head of worker in future on the basis of principle individual approach to each worker. The development this conception includes new hypothesis about reason constructive or destructive behavior of worker.